Schools of Music as Social Institutions in Service to Society - Rice, Timothy (MUSICultures, 2023)
Faculties and schools of music in Canada and the United States define their missions narrowly; their curricula continue to be devoted almost exclusively to a music culture created in Europe and exported to colonial and postcolonial settings around the world. These institutions teach an exclusionary aesthetic philosophy rooted in white supremacy, one that results in the unethical exclusion of musicians and musical cultures created by the communities and societies that universities are meant to serve. After analyzing the content of, and the ideas behind, various course syllabi, the author outlines pathways for creating aesthetically and ethically inclusive and anti-racist curricula in music history and music appreciation at music faculties and schools of music in Canada and the United States.